Automatic Control for Stewart Platform - SAHAT MARULITUA (NIM : 13113134), DAVID
The development of industrial automation technology currently progresses quickly. One of the technologies that support industrial automation is manipulator robot. One example of manipulator robot is the Stewart Platform robot. Stewart Platform robot is a robot that can move in the three-dimensional field consisting of the base, platform, and linear actuator. Currently the Production Laboratory of the Mechanical Engineering Department ITB is developing a Stewart Platform robot which has six linear actuators. This research developed an automatic control system for Stewart Platform robot with PID control using Arduino microcontroller. The control system is designed using two feedback data, which are position data and velocity data of linear actuator. The position data is obtained from the linear potentiometer sensor, while the velocity data is obtained from the differentiated position data. The length of each actuator is obtained by kinematic inverse. End position parameters, acceleration and deceleration time, and final speed is set through the user interface. The interface program is developed using Visual Studio 2015. The Stewart Platform robot system has been able to run quite well, however, there are still some small errors. Further development is still required to be done to improve the control system. Errors generally occur due to noise from the measurement system and it needs to be improved.